2006
DOI: 10.1111/j.1468-3083.2006.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of chronic illness in psoriasis vulgaris patients

Abstract: The results obtained seem to confirm that personal resources play an important role in acceptance of chronic illness. Enhancement of optimism, and minimizing one's conviction that one's health depends on others could lead to higher acceptance of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 44 publications
2
37
1
4
Order By: Relevance
“…It is possible that people resort to religion when helplessness and hopelessness are profound, and thus religion may be a marker of severe psychological suffering. Our data add to the available evidence that self-esteem, self-efficacy, sense of coherence, assertive behavior and active coping strategies are crucial resources in psoriatic patients, both for accepting the disease and establishing a therapeutic alliance with the caregiver (25). On the other hand, psoriatic patients who use passive coping strategies have a worse quality of life (26).…”
Section: Discussionmentioning
confidence: 69%
“…It is possible that people resort to religion when helplessness and hopelessness are profound, and thus religion may be a marker of severe psychological suffering. Our data add to the available evidence that self-esteem, self-efficacy, sense of coherence, assertive behavior and active coping strategies are crucial resources in psoriatic patients, both for accepting the disease and establishing a therapeutic alliance with the caregiver (25). On the other hand, psoriatic patients who use passive coping strategies have a worse quality of life (26).…”
Section: Discussionmentioning
confidence: 69%
“…15,16 The quality of life was affected in psoriasis as well as neurodermatitis however the impact was significantly severe in patients of neurodermatitis in this study. Whereas in studies supports the impact of psoriasis on the quality of life, while Kabbur H et al study reveals that the stress-reaction has impact on the exacerbations of psoriasis which in turn has effect on quality of life.…”
Section: Discussionmentioning
confidence: 74%
“…On similar lines, Zalewska et al (2007) suggested that personal resources play an important role in acceptance of chronic illness. Enhancement of optimism, and minimizing one's conviction that one's health depends on others could lead to higher acceptance of skin disease.…”
Section: Discussionmentioning
confidence: 96%